ANALISIS VEGETASI POHON DI KAWASAN HUTAN BATU BUSUAK PADANG - Yuhendri, Rival; Mukhtar, Erizal; Safitri, Elza (STKIP PGRI Sumbar, 2013)
ABSTRACTBatu BusuakÂ forest area is located in the district Pauah of Padang. On July 24th landslide and flood have been destroyed to the forest and caused the forest structure changes. Based on above reason it is important to analyze the forest structure in Batu Busuak Padang. in order to clarify vegetation analyzes we applied transect along undegraded and degraded area using the quadrant method. The tree composition at degraded areas was 22 families, 49 species and 200 individuals. Further more 31 families, 84 species and 200 individual were found at degraded area. Areca chatecu has the highest important value index on degraded area was 20.64%. Porterandia anisophylla was the lowest one (1.7%). Xerospermum sp has the highest important value index at undegraded area (15.27%) and Micros florida was the lowest one (1.24%).Â